FÂRÂBÎ’DE YÜKLEMLİ KIYASLAR - Halil İmamoğlugil (İslami İlimler Dergisi)
In this article, we examined how Alfarab approached to the subject of categorical syllogism within scope of his works entitled “Kitāb al-Kıyās al-Sağīr” and “Kitāb al-Kıyās”. Alfarab defined syllogism as Aristoteles did it, and after defining it, made analysing of that definition, and then explained each of the terms which composed the definition in that analysing. Categorical syllogisms were the main syllogisms that Alfarab emphasised. Before him, Aristoteles also took up those syllogisms. He examined it in the Organon and did not mention the syllogisms composed of conditional propositions. Alfarab noted that categorical syllogisms had to have same special conditions in terms of quality and quantity for giving conclusions of each figure of the categorical syllogisms, and exemplifid the moods giving conclusion in every figure.